Growth, yield and quality of cluster bean (Cyamopsis tetragonoloba) as influenced by integrated nutrient management under alley cropping system - SHARMA, PANKAJ; MEENA, RAM SWAROOP; KUMAR, SUNIL; GURJAR, D S; YADAV, GULAB SINGH; KUMAR, SANDEEP (The Indian Journal of Agricultural Sciences, 2019)
A field study was conducted to assess the impact of integrated nutrient management (INM) on cluster bean (Cyamopsis tetragonoloba L.) under alley cropping system in kharif 2018 at Banaras Hindu University, Mirzapur (UP). The six treatments, viz. 75% RDF + Rhizobium, 75% RDF + Biochar + Rhizobium, 100% RDF + Rhizobium, 75% RDF + farm yard manure + Rhizobium, 100% RDF + Vermicompost + Rhizobium and 75% RDF + pressmud + Rhizobium were laid out in randomized block design with four replications. Highest growth parameters, viz. plant height, dry matter accumulation, number of nodules/plant, dry weight of nodules, crop growth rate, leaf area index, chlorophyll content, number of secondary branches/plant, and the highest yield attributes and yield, viz. number of pods/plant, length of pod, number of seeds/pod, test weight, seed yield (922.60 kg/ha), straw yield (2496.10 kg/ha), biological yield (3418.70 kg/ha) were recorded with the application of 75 % RDF + pressmud + Rhizobium. Similarly, the highest NPK content and their uptake, protein and gum content, and economics, viz. gross return (77241 â‚¹/ha), net return (46461 `/ha) were seen with the application of 75% RDF + pressmud + Rhizobium, while the highest B: C ratio (1.59) was observed with the application of 100% RDF+ Rhizobium.